Development drivers of the water-energy-food nexus in the Gulf Cooperation Council region. Issue 5 (4th July 2019) - Abulibdeh, Ammar; Zaidan, Esmat; Al-Saidi, Mohammad
ABSTRACT: This article analyses water, food, and energy security in the Gulf Cooperation Council (GCC) countries using the water-energy-food (WEF) nexus approach. The innovative focus is on identifying past and future development-based drivers of water-energy-food integration in the region. The study presents a critical review of WEF nexus in the Gulf region and identifies links to sustainable development in this area. It concludes that integrating water, energy, and food resources within the nexus is crucial for GCC nations to accomplish resource security and sustainable development.